Methodology and theory building in MIS research - LIGHTNER, Nancy (Institutional Knowledge at Singapore Management University, 1998)
This paper reports on the stage of maturity of MIS research according to the McGrath (1979) model, as evidenced by the theory building occurring in two top MIS research journals. While MIS as a discipline continues to grow, its development depends on establishing a cumulative tradition of good research (Keen 1980). Of the published papers surveyed that are relevant to theory building, 81% of them relate to theory development, while 18% address theory testing. Of the papers involving data collection, more than half use field studies as the methodology. In order to advance MIS as a mature field, it is hoped that MIS researchers consider these findings when developing future research agendas.